The Effect of Usability, Security and Quality Information on Interest in Buying Cinema Tickets Through the Tix ID Application from an Islamic Business Perspective - Purbandari, Elok Fevia; Suhendar, Suhendar; Verawati, Heni (Institut Agama Islam Sunan Giri Ponorogo, 2025)
In the era of Industry 4.0 which is marked by technological advances such as the Internet of Things (IoT), artificial intelligence (AI) and big data, trading companies are encouraged to adopt technology to stay relevant and competitive. Tix Id application still has many negative user comments such as when trying to exchange tickets that have been purchased through the application, the cellphone number is not found while the user's cellphone number is still active and when the user contacts customer service, the money that should have been returned to the digital wallet account does not return. The study aims to test the direct influence of Usability, Security and Quality Information on Interest in Buying Cinema Tickets Through the TIX ID Application. This study uses a quantitative approach. The sample collection technique used in this study is Non-probablity. The technique used in sampling is purposive sampling using the Slovin formula with a sample size of 100 samples. The results obtained Usability, security and quality information have a positive and significant repercussion on the interest in buying cinema tickets for TIX ID Application Users in Bandar Lampung City. Interest in purchasing cinema tickets is permitted as long as the content being watched is halal, educational and does not contain elements of sin, and is done wisely and not excessively (israf).